Describing the experience of livestock producers from Ohio, USA with ticks and associated diseases - Andreas Eleftheriou; Samantha Swisher; Andréia Arruda; Amanda Berrian; Risa Pesapane (BMC, 2023)
Abstract Background As tick ranges expand across North America, the risk of tick bites and tick-borne diseases (TBDs, i.e. diseases or syndromes associated with ticks) rises for humans and animals, making prevention critical. Several U.S. studies have examined knowledge, attitudes, and practices regarding ticks and TBDs for various cohorts of people. However, among occupational groups with high exposure risk from ticks and TBDs are livestock producers, of which we know little about. To help address this gap, an electronic questionnaire was distributed to livestock producers in Ohio, U.S, a state with a robust agricultural sector. Methods We generated descriptive statistics and conducted a multiple correspondence analysis followed by hierarchical clustering on principal components to identify producers with similar response profiles. Results Responses from 57 producers showed that most (52.6%) think the American dog tick (Dermacentor variabilis) is found in Ohio but are unsure about other species. Although several TBDs are present in Ohio, most (> 50%) producers were unsure or unaware of their presence. Interestingly, most (54.4%) thought ticks pose major health risks for their livestock but fewer (49.1%) thought the same for humans. Regardless, most producers did employ at least one prevention method for themselves (96.5%) and their animals (82.5%). Cluster analysis (n = 48) identified three groups: the largest (n = 21) was considered "aware and cautious" consisting primarily of farm owners. The others generally practiced less prevention and consisted primarily of farm employees. Conclusions Our findings indicate that producers in Ohio practice prevention for themselves and their livestock, but demonstrate gaps in knowledge (e.g., TBD occurrence) and attitudes (e.g., health risks) that could be addressed via educational formats we found producers preferred (e.g., extension materials), to encourage informed prevention. This is especially important for farm employees that may practice less prevention because of lower awareness. Our study can guide others in regions faced with similar tick and TBD risks to protect occupational and livestock health.